Pseudoginsenoside-F11 Accelerates Microglial Phagocytosis of Myelin Debris and Attenuates Cerebral Ischemic Injury Through Complement Receptor 3. (1st February 2020) - Liu, Yinglu; Wu, Chunfu; Hou, Zongjuan; Fu, Xiaoxiao; Yuan, Linlin; Sun, Shibo; Zhang, Haotian; Yang, Depeng; Yao, Xuechun; Yang, Jingyu
Graphical abstract: Highlights: PF11 enhances the OGD-induced promotion of myelin debris phagocytosis by microglia. PF11 decreases the release of OGD-induced microglial pro-inflammatory factor. PF11 promotes microglial phagocytosis of myelin debris through CR3. PF11 attenuates cerebral ischemic injury through CR3. Abstract: After ischemic stroke, the degenerated myelin caused by ischemic injury cannot be rapidly cleared away by microglia and interferes with the recovery process. Complement receptor 3 (CR3, CD11b/CD18), belonging to β2 integrin family primarily expressed in phagocytes, is involved in the microglial phagocytosis of myelin debris. We previously found that pseudoginsenoside-F11 (PF11), an ocotillol-type saponin, exerts neuroprotective effects against ischemic stroke and neuroinflammation. In the present study, we investigated the promotion of PF11 on oxygen-glucose deprivation (OGD)-induced microglial phagocytosis of myelin debris, the neuroprotection of PF11 on permanent middle cerebral artery occlusion (pMCAO)-induced ischemic stroke, and the possible role of CR3. The results indicated that PF11 (50 μM) accelerated the OGD-induced promotion of myelin debris phagocytosis by microglia in the early stage of OGD (2 h, 4 h, 8 h), which was significantly inhibited by anti-CD11b mAb or down-regulated by CD11b-specific siRNA. Meanwhile, PF11 strengthened the OGD-activated RhoA/ROCK signaling associated with the internalization during myelin debris phagocytosis through CR3. Consistently, the anti-CD11b mAb could markedly attenuated the nrueoprotective effects of PF11 (12 mg/kg, i.v.) on infarction and brain edema, neurological functions and loss of neurons of pMCAO rats. These findings suggest that PF11 accelerates the phagocytosis of myelin debris by microglia mainly through CR3, which may likely contribute to its neuroprotection against ischemic stroke.